The Development of Web-Based Thai Teaching Training Course by Using Tales for Teachers of Office of the Basic Education Commission - Doungjino, Teerat; Pattanasith, Sunchai (Journal of Information and Learning [JIL], 2020)
The purposes of this research were (1) to development of Web-Based Training course by Using Tales of Thai Teaching for Teachers of Office of the Basic Education Commission, which are effective according to the criteria 85/85; (2) to compare the training achievement with pre-training scores; and (3) to study of the teachers' satisfaction. The sample was selected from 30 Thai language teachers in grade 1-3 under the Office of Educational Service Area, Pattani, Yala and Narathiwat provinces by using simple random methods. The research instruments were composed of (1) Training website course by using tales of thai teaching; (2) Training website quality evaluation form; (3) Pre-post training test; and (4) Assessment form for training satisfaction. Data were analyzed using statistics such as percentage, mean, standard deviation. And t-test statistics (a = 0.05). The results of the study revealed that 1) the quality of the training website course of Thai Teaching by Tales for Teachers of Office of the Basic Education Commission By educational technology experts was the highest quality ( =4.56, S.D.=0.10) and the efficiency of E1/E2 is 84.81/84.44 in order to based 85/85; 2) The average score after using the Web-Based Training for Thai Teaching by Tales was significantly higher than before the training at 0.05 level 3) Trainees satisfied with using the Web-Based Training for Thai Teaching by Tales in a high level ( =4.46 , S.D.=0.49).